Epstein-Barr virus (EBV) reactivation and therapeutic inhibitors. Issue 10 (17th July 2019) - Kerr, Jonathan R
Abstract : Epstein-Barr virus (EBV) is a ubiquitous human virus which infects almost all humans during their lifetime and following the acute phase, persists for the remainder of the life of the individual. EBV infects B lymphocytes leading to their immortalisation, with persistence of the EBV genome as an episome. In the latent phase, EBV is prevented from reactivating through efficient cytotoxic cellular immunity. EBV reactivates (lytic phase) under conditions of psychological stress with consequent weakening of cellular immunity, and EBV reactivation has been shown to occur in a subset of individuals with each of a variety of cancers, autoimmune diseases, the autoimmune-like disease, chronic fatigue syndrome/myalgic encephalitis and under other circumstances such as being an inpatient in an intensive care unit. Chronic EBV reactivation is an important mechanism in the pathogenesis of many such diseases, yet is rarely tested for in immunocompetent individuals. This review summarises the pathogenesis of EBV infection, EBV reactivation and its role in disease, and methods which may be used to detect it. Known inhibitors of EBV reactivation and replication are discussed, including drugs licensed for treatment of other herpesviruses, licensed or experimental drugs for various other indications, compounds at an early stage of drug development and nutritional constituents such as vitamins and dietary supplements.